PEMANFAATAN ETNOMATEMATIKA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS IV SDN 1 SENGGRONG - Oktavia Nurhana Zulfa; Anggit Grahito Wicaksono; Ema Butsi Prihastari (Universitas Borneo Tarakan, 2024)
This research was conducted at state elementary school 1 Senggrong Boyolali. The subjects in this study were 4th grade students. The research conducted was included in Classroom Action Research which was conducted with two cycles, each cycle consisting of 4 meetings. Interviews, observations, documentation were the techniques used in data collection. After all the data was collected, the researcher processed the data using comparative descriptive analysis techniques. Ethnomathematics has been proven to increase the activity and learning outcomes of mathematics, this can be seen in the pre-cycle data, only 40% achieved a score of 75 as the Minimum Completeness Criteria. After the implementation of cycle 1, 60% of students passed and the implementation of cycle 2 succeeded in increasing the percentage of student completion to 80%. Referring to the results obtained, it can be concluded that the use of picture card teaching materials based on ethnomathematics has been proven to increase the activity and learning outcomes of 4th grade students at state elementary school 1 Senggrong Boyolali.